Инженерно-геодезические изыскания для строительства ЛЭП - Нефедов В. В. Владимир Владимирович; Любимов О. М. Олег Михайлович; Шумихин Ю. Н. Юрий Николаевич; Евтеев А. Г. Анатолий Григорьевич (Москва, Недра, 1990)
Авт. указаны на обороте тит. л.